Comunidades Eclesiais de vizinhança: Um novo jeito de ser igreja. Um estudo de caso na comunidade São João Batista na periferia de Fortaleza - Queiroz, Paulo Wescley Almeida de (2012)
The present work is about a case study on the Neighbourhood Church Communities, a type of religious association of living of the Catholic Church in São João Batista Community, located in a religious area, in the Palmeira's Parish, Archdiocese of Fortaleza, located geographically in Sítio São João, Jangurussu, outskirts of Fortaleza. The Catholic Church felt the need to develop strategies to combat the post-modern factors that would be keeping off masses, therefore, motivated the creation of small groups in parishes in order to appreciate the laity and to promote the decentralization of pastoral work. This qualitative study was an attempt, through the thoughts of the Catholic Church, by theirdocuments and authors and participant observation, to understand the action of this phenomenon from the experiences of its participants, of the religious practices in these groups and how these experiences influenced the social and affective relationships of these neighbors. The creation of CEV's motivated the participation of community people in masses, in the quest to experience the sacraments, and influenced the daily lives of people who started to attend meetings, engagement in pastoral work and allowed rapprochement between them, "taking them from the anonymity. "